Sexuality today : - Kelly, Gary F. (McGraw-Hill, 2004)
Gary Kelly continues to provide the most up-to-date, balanced view of sexuality in the market. "Sexuality Today: The Human Perspective, Updated 7th Edition" carefully balances the psychological, biological/physiological, and social elements of human sexuality, integrating all of the latest research findings and social trends. Kelly's balanced approach is also evident when he presents various sides of controversial topics in a neutral voice. Students are trusted to weigh the facts with their own ideas and the views of others in a class so that they may understand and clarify their personal beliefs and values. Case studies are provided to help students think through their options and values relating to the personal sexual decisions they will make throughout their lives. Kelly provides students with questionnaires to evaluate their own behavior immediately following the case to encourage students to make the course personal. The end result of these efforts is a text that will help students understand their own behavior and take the mystery out of sexuality. The engaging writing style and inexpensive price have made this text a student favorite throughout the last seven editions.